Analisis Konsep, Teori dan Lingkup Politik Pendidikan - Dessi Asdrayany; Muhamad Najmi Muhajir; Anis Fauzi; Ahmad Qurtubi (Departement of Mathematics Education, 2023)
This research uses a qualitative research type with a library research approach by digging up information through the literature regarding concepts, theories and the political scope of education to answer the focus of the study in this study. This study examines political concepts, political theory, political spheres and educational politics. Education is an effort to develop the human potentials of students, both their physical potential, their creative potential, taste and intention, so that this potential becomes real and can function in their life journey. The basis of education is a universal human ideal. Education aims to prepare a personal balance, unity. organic, harmonious, dynamic. in order to achieve the goals of human life. This can be understood considering that the higher the opportunity for a person or society to get an education, the higher the opportunity for a person or society to read, compare, evaluate, as well as criticize the space of ideals and political reality. Thus, the key to public political education actually lies in the politics of public education. Educational politics are all policies of the government of a country in the field of education in the form of laws or other regulations to organize education in order to achieve the goals of the country. The educational politics (siyâsah atta‘lîm) of a country is largely determined by the ideology (view of life) that the country carries.